RERANGKA PENGATURAN TEKNOLOGI INFORMASI UNTUK ORGANISASI DI INDONESIA - Kridanto Surendro (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2004)
Integration ofinfonnation system in organization’s business is a critical thing in titr‘s inionnatrbn economy are. Hence, informatron system will no longerbe seen as an enabler to achieve organization's strategy, moreover, as an integral part of the strategy itself. To be able to gain competitive advantage, infonnation technology needs to be aligned with the organisation ‘s goal. Questions arise for organisation that implement information technology are how far the implementation of information technology has achieved the business goal? What is performance of informationtechnology processess in organisation? And what is the condition of information technology processess?This paper will explain about the development of information technology framework for organization in lndonesia. COBIT is used as a reference when develop this homework. The framework is developed through the observation over real implementation of infonnation technology in public hospital and university. Finally we found that the most important information technology processess are 20 processess.Keywords: framework, Information Technology Govemance. process. business